SYNTHESIS AND IN-VITRO ANTIMICROBIAL ACTIVITY OF NOVEL AMINOPHOSPHINIC ACIDS CONTAINING CYCLOBUTANE AND 1,3-THIAZOLE - Koparir, Pelin; Karaarslan, Muhsin; Orek, Cahit; Koparir, Metin (Taylor & Francis Ltd, 2011)
The compounds {[4-(3-methyl-3-aryl(mesityl-phenyl-tetralino)cyclobutyl)-1,3-thiazol-2-yl]amino}(aryl)methyl-phosphinic acids 2a-l were prepared by condensation of 2-amino-4-(3-aryl(mesityl-phenyl-tetralino)-3-methylcyclobutyl)thiazoles 1a-c with various aromatic aldehydes and hypophosphorous acid through a one-pot reaction. The characterizations of these compounds were obtained by elemental analyses, infrared (IR) spectra, and H-1, C-13, and P-31 NMR (nuclear magnetic resonance) techniques. The synthesized compounds were tested in vitro against one Gram-positive and two Gram-negative bacterial strains, one mycobacterial strain, and a fungus Candida albicans. Compound 2f showed significant activity against Staphylococcus aureus, whereas the others had no remarkable activity on this strain. Compound 2g was found to be more active than the others against Mycobacterium fortuitum at an MIC (minimum inhibitory concentration) value of 32 mu g/mL. The antibacterial and antifungal activities of 2a-l were also compared with various standard drugs.
Keywords: Aminophosphinic acids; cyclobutane; thiazole